Do dynamic‐based MR knee kinematics methods produce the same results as static methods?. Issue 6 (27th July 2012) - d'Entremont, Agnes G.; Nordmeyer‐Massner, Jurek A.; Bos, Clemens; Wilson, David R.; Pruessmann, Klaas P.
Abstract: MR‐based methods provide low risk, noninvasive assessment of joint kinematics; however, these methods often use static positions or require many identical cycles of movement. The study objective was to compare the 3D kinematic results approximated from a series of sequential static poses of the knee with the 3D kinematic results obtained from continuous dynamic movement of the knee. To accomplish this objective, we compared kinematic data from a validated static MR method to a fast static MR method, and compared kinematic data from both static methods to a newly developed dynamic MR method. Ten normal volunteers were imaged using the three kinematic methods (dynamic, static standard, and static fast). Results showed that the two sets of static results were in agreement, indicating that the sequences (standard and fast) may be used interchangeably. Dynamic kinematic results were significantly different from both static results in eight of 11 kinematic parameters: patellar flexion, patellar tilt, patellar proximal translation, patellar lateral translation, patellar anterior translation, tibial abduction, tibial internal rotation, and tibial anterior translation. Three‐dimensional MR kinematics measured from dynamic knee motion are often different from those measured in a static knee at several positions, indicating that dynamic‐based kinematics provides information that is not obtainable from static scans. Magn Reson Med, 2013. © 2012 Wiley Periodicals, Inc.